Taxonomic considerations on the genus Ophthalmoglipa Franciscolo, 1952 (Coleoptera: Mordellidae) with description of two new species - Ruzzier, Enrico (Zootaxa, 2015)
In the present paper Ophthalmoglipa Franciscolo 1952 is critically analysed. The status of Ophthalmoglipa aurocaudata (Fairmaire 1897) sensu Franciscolo (1952) as the type species is discussed and redefined. Ophthalmoglipa leblanci. n. sp. from São Tomé and Ophthalmoglipa horaki n. sp. from Principe Island are herein described.